Pengaruh IHSG, Nilai Tukar, BI Rate, dan Harga Emas terhadap ISSI - Irtifa Umi Azizah; Muchammad Ilham Syarifudin; Aqim Adlan (Journal of Economics and Business Aseanomics, 2025)
The Indonesia Stock Exchange has 45 indices that reflect various market segments, including the Composite Stock Price Index (IHSG) as the main indicator of the overall market, and the Indonesian Sharia Stock Index (ISSI) which represents stocks based on sharia principles. This study aims to analyze the effect of the IHSG, the rupiah exchange rate against the US dollar, the Bank Indonesia benchmark interest rate (BI Rate), and world gold prices on the movement of the ISSI. The research method used is a quantitative approach with multiple linear regression analysis using time series data for the period 2022–2024 processed using EViews software. Data were obtained from official sources such as the Indonesia Stock Exchange and the Central Statistics Agency. The results of the study show that simultaneously the four variables, namely the IHSG, BI Rate, Exchange rate, and world gold price, have a significant effect on the ISSI. However, partially, only the IHSG has a positive and significant effect on the ISSI. Meanwhile, the exchange rate, BI Rate, and world gold price do not show a statistically significant effect. This finding confirms that the movement of the ISSI is more sensitive to the dynamics of the domestic stock market compared to external global macroeconomic factors